Waste to biogas through anaerobic digestion: Hydrogen production potential in the developing world - A case of Bangladesh - Khan, Imran (International journal of hydrogen energy, 2020)
Waste management is one of the greatest global challenges, for which one reason is the composition of waste, which varies not only from one region to another but also over time. Recent studies considered waste treatment options for the developed world, where management schemes include waste to hydrogen generation. Although there is great potential for producing hydrogen from waste (e.g. biogas) in the developing world, this has received less attention. This study explores hydrogen production potential from waste in the developing world, particularly focusing on Bangladesh. Results show that anaerobic digestion is the most suitable waste management technology for the developing world predominantly due to waste's composition. The waste composition is dominated by organic food wastes (varying between 50% and 87%), of which the moisture content is more than 50%, thus being unsuitable for self-combustion. National energy policy making should consider this potential source of energy/hydrogen towards a sustainable future. •Explores hydrogen production potential in the developing economies.•In developing countries, the organic food wastes vary between 50% and 87% in the waste composition.•The calorific value of organic waste is very low as it contains 57%–67% moisture.•Anaerobic digestion is a suitable technology to produce biogas from the organic waste.•There is a great potential to produce green hydrogen from biogas in the developing world.